Adiabatic control of surface plasmon-polaritons in a 3-layers graphene curved configuration. (February 2018) - Huang, Wei; Liang, Shi-Jun; Kyoseva, Elica; Ang, Lay Kee
Abstract: In this paper, we utilize coupled mode theory (CMT) to model the coupling between surface plasmon-polaritons (SPPs) between multiple graphene sheets. By using the Stimulated Raman Adiabatic Passage (STIRAP) Quantum Control Technique, we propose a novel directional coupler based on SPPs evolution in three layers of graphene sheets in some curved configuration. Our calculated results show that the SPPs can be transferred efficiently from the input graphene sheet to the output graphene sheet, and the coupling is also robust that it is not sensitive to the length of the device configuration's parameters and excited SPPs wavelength. Graphical abstract: Image 1